MYOSITIS OSSIFICANS - MRI AND CT FINDINGS - Bundovska, Smiljana; Stefanovska, Elizabeta (Journal of Morphological Sciences, 2020)
Myositis ossificans (MO) is a benign, self-limiting process that results in intramuscular bone proliferation.We report a case of a 16-year-old male who presented with a painless mass on the left arm and an increasing lump, without a history of trauma. Plain CT and MRI with contrast exams were done. The mass was extirpated and biopsy was done. Histopathological findings referred to the diagnosis of myositis osificans. Keywords: myositis osificans, calcifications, soft-tissue mass